Design and Construction of Plastic Chair Armrest Cover Piercing Dies at PT. XYZ - Wilarso; Asep Dharmanto; Giardyan Komara; Asep Saepudin; Mujiarto (Universitas Medan Area, 2026)
The armrest cover on the chair is produced using the vacuum forming method and so far the line cutting and hole making process is done manually using a hand grinder, thus potentially causing quality inconsistencies and low productivity. The armrest cover made of ABS plastic has a hole dimension of 37 mm × 22 mm, a thickness of 3 mm, and a circumference of 119.27 mm, with a shear strength value of 67 MPa based on Proto XYZ data. Calculations show that the minimum force required for the punching process is 8.46 tons. This study aims to design and manufacture piercing dies for the armrest cover punching process to obtain precise cutting results and increase production output. The dies were made using a CNC milling machine with the help of Autodesk Fusion 360 software, then the dies were tested using a 15-ton capacity press machine. The test results showed that the resulting holes met the specified dimensional standards. The implementation of these piercing dies significantly increased production capacity, from 90 sets per shift in the manual process to 1,920 sets per shift using piercing dies. Thus, the use of piercing dies has proven effective in increasing the precision and efficiency of the plastic armrest cover manufacturing process.